Faktor-faktor yang berhubungan dengan kejadian stunting pada balita - Sari, Cucuk Kunang; Sari, Yunita (Holistik Jurnal Kesehatan, 2023)
Background: Stunting is a problem that occurs in children's growth and development due to poor nutrition, recurrent infections, and inadequate psychosocial support. The word stunting is given to children whose height for age is below two standard deviations of the median child's growth. The stunting process can begin when the fetus is in the womb and will become visible when the child enters the second year of age. According to the World Health Organization, the prevalence of stunted toddlers is 22.9% and the nutritional status of under-fives is the cause of 2.2 million of all under-five deaths worldwide. Nearly half the death rate in children under 5 years in Asia and Africa is caused by malnutrition. This causes the deaths of three million children per year. Indonesia is in 17th position out of 117 countries that have nutritional problems among children under five, namely stunting, wasting and being overweight. Based on the results of Basic Health Research in 2018, the prevalence of stunting in toddlers was 30.8% with the very short category 11.5% and the short category 19.3%. Stunting data in 2018 decreased compared to stunting data in 2013 of 37.2%.Purpose: To determine the factors associated with the incidence of stunting.Method: This type of quantitative research uses an analytical survey method with a case control or retrospective study design, namely an analytical study of the effects of disease or case events identified at this time and then risk factors identified as existing or occurring in the past. The research was carried out in the working area of the Jambe Community Health Center, Tangerang Regency in June-August 2022 with the research sample being 68 toddlers taken using a total sampling technique. The inclusion criteria for the case group were toddlers aged 2-5 years who were registered as stunting toddlers, parents were willing to be respondents, could communicate well, and had a cellphone. Meanwhile, the inclusion criteria for the control group were that toddlers aged 2-5 years were registered as normal toddlers, parents were willing to be respondents, could communicate well, and had a cellphone. The exclusion criteria for the case and control groups were toddlers born with LBW and congenital defects.Results: Based on vaccination status, the statistical test with chi-square p-value was 0.473 (>0.05), so it can be concluded that there is no relationship between vaccination status and the incidence of stunting. Statistical test of history of infectious disease with a chi-square p-value of 0.000 (<0.05), meaning that there is a relationship between history of infectious disease and the incidence of stunting. According to the exclusive breastfeeding variable, the resulting chi-square p-value is 0.000 (<0.05), meaning that there is a relationship between exclusive breastfeeding and the incidence of stunting. Apart from that, there is a relationship between parental height, maternal knowledge, and parental parenting patterns on the incidence of stunting.Conclusion: Based on seven variables, namely, gender, vaccination status, history of infectious diseases, exclusive breastfeeding, parents' height, mother's knowledge, and parenting patterns, only the vaccination status variable has no relationship to the incidence of stunting. In fact, whether toddlers are fully vaccinated or not, they are equally at risk of contracting infectious diseases if they are not balanced with good eating habits.Keywords: Exclusive Breastfeeding; Parenting; Stunting; Vaccination.Pendahuluan: Stunting merupakan permasalahan yang terjadi pada tumbuh dan kembang anak dikarenakan mengalami gizi buruk, adanya infeksi yang berulang, dan dorongan psikososial yang kurang memadai. Kata stunting diberikan pada anak yang tinggi badannya sesuai usia berada dibawah nilai dua standar deviasi median pertumbuhan anak. Proses stunting dapat dimulai saat janin dalam kandungan dan akan terlihat ketika anak memasuki usia di tahun kedua. Menurut World Health Organization, prevalensi balita stunting sebesar 22.9% dan keadaan gizi balita pendek menjadi penyebab 2.2 juta dari seluruh penyebab kematian balita di seluruh dunia. Hampir setengah tingkat kematian pada anak-anak di bawah 5 tahun di Asia dan Afrika disebabkan oleh kekurangan gizi. Hal ini menyebabkan kematian tiga juta anak per tahun. Indonesia berada dalam posisi 17 negara dari 117 negara yang memiliki permasalahan gizi pada balita yaitu stunting, wasting, dan kelebihan berat badan. Berdasarkan hasil Riset Kesehatan Dasar pada tahun 2018, prevalensi stunting pada balita sebesar 30.8% dengan kategori sangat pendek 11.5% dan kategori pendek 19.3%. Data stunting tahun 2018 tersebut sudah terjadi penurunan dibandingkan data stunting tahun 2013 sebesar 37.2%.Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan kejadian stunting.Metode: Jenis penelitian kuantitatif menggunakan metode survey analytic dengan desain atau rancangan case control atau retrospective study yaitu suatu penelitian analytic efek penyakit atau kejadian kasus diidentifikasi saat ini kemudian faktor risiko diidentifikasi ada atau terjadi pada waktu yang lalu. Penelitian dilaksanakan di wilayah kerja Puskesmas Jambe Kabupaten Tangerang pada bulan Juni-Agustus tahun 2022 dengan sampel penelitian adalah 68 balita diambil dengan teknik total sampling. Kriteria inklusi pada kelompok kasus yaitu balita usia 2-5 tahun tercatat sebagai balita stunting, orangtua bersedia menjadi responden, dapat berkomunikasi dengan baik, dan memiliki handphone. Sedangkan kriteria inklusi kelompok kontrol yaitu balita usia 2-5 tahun tercatat sebagai balita normal, orangtua bersedia menjadi responden, dapat berkomunikasi dengan baik, dan memiliki handphone. Kriteria eksklusi kelompok kasus maupun kontrol adalah balita yang lahir dengan BBLR dan cacat bawaan.Hasil: Berdasarkan status vaksinasi, uji statistik dengan chi-square nilai p-value sebesar 0.473 (>0.05), sehingga dapat disimpulkan bahwa tidak ada hubungan status vaksinasi dengan kejadian stunting. Uji statistik riwayat penyakit infeksi dengan chi-square nilai p-value yang dihasilkan sebesar 0.000 (<0.05), artinya ada hubungan riwayat penyakit infeksi terhadap kejadian stunting.  Menurut variabel ASI eksklusif dengan chi-square p-value yang dihasilkan sebesar 0.000 (<0.05), artinya ada hubungan pemberian ASI eksklusif dengan kejadian stunting. Selain itu, ada hubungan tinggi badan orang tua, pengetahuan ibu, dan pola asuh orangtua terhadap kejadian stunting.Simpulan: Berdasarkan tujuh variabel yakni, jenis kelamin, status vaksinasi, riwayat penyakit infeksi, pemberian ASI eksklusif, tinggi badan orangtua, pengetahuan ibu, dan pola asuh pemberi makanan hanya variabel status vaksinasi yang tidak memiliki hubungan terhadap kejadian stunting. Sebenarnya baik balita yang divaksinasi lengkap maupun tidak, sama-sama beresiko terkena penyakit infeksi jika tidak diimbangi dengan pola asuh makan yang baik.